Crossing the line: Drawing as Babel Fish. Issue 2 (1st December 2016) - Casey, Sarah; Davies, Gerry
This article examines the emergence of illustrative practices among fine artists to achieve a particular mobility, one that enables them to gather, synthesize and communicate information across diverse environments, locations and communities. The article recognizes a growing appetite among contemporary illustrators and artists to work collaboratively and across previously separate disciplines, and focuses on artists leaving the studio to seek out ever more responsive applications of drawing. This reveals a hybrid, fluid approach in drawing, a new sensitivity in which drawing is used by artists as a way of analysing, communicating and reflecting upon aspects of lived experience, some of which might normally be the province of other research professionals. We explore how these 'itinerant' artists use drawing to translate into graphic form information, ideas and practices from other fields of activity – for instance, oceanography (Peter Matthews), medicine (Julia Midgley) and political activism (Jill Gibbon). While these contemporary practices are at the cutting edge, we discuss their direct lineage to Ruskin's Elements of Drawing (1857) and his belief in the use of drawing to interrogate the world and our position in it. We argue that this underacknowledged mode of practice is timely and significant for a globalized interdisciplinary research community because it reveals drawing's capacity to intercede, for problem-solving and for building relationships across otherwise disparate communities and areas of expertise.